2004
DOI: 10.1111/j.1600-0722.2004.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of success and failure of behavior modification as treatment for dental anxiety

Abstract: Behavior modification techniques are effective in the treatment of extreme dental anxiety, but their success is by no means absolute. In the present article, the Corah Dental Anxiety Scale (DAS), the self-report symptom inventory SCL-90R and a questionnaire accessing subjects' daydreaming styles (the Short Imaginal Process Inventory) were used to develop possible predictive measures for success and failure of behavior modification as a treatment for dental fear. The patients' level of distractibility and mind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…27,28 Techniques that can alter the behavior of the patients could prove useful in reducing severe anxiety but even they cannot guarantee total success. 29 Counseling sessions for these severely anxious students conducted by trained professionals could prove helpful in decreasing their anxiety level. In addition, the authors recommend 'Exposure therapy' for junior dental students which is a type of behavior therapy intended to reduce the anxiety by the exposure of feared object or procedure repeatedly.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Techniques that can alter the behavior of the patients could prove useful in reducing severe anxiety but even they cannot guarantee total success. 29 Counseling sessions for these severely anxious students conducted by trained professionals could prove helpful in decreasing their anxiety level. In addition, the authors recommend 'Exposure therapy' for junior dental students which is a type of behavior therapy intended to reduce the anxiety by the exposure of feared object or procedure repeatedly.…”
Section: Discussionmentioning
confidence: 99%
“…D entally anxious patients tend to present with long-term avoidance behavior and seek treatment only when severe pain is experienced. [1][2][3][4] This avoidance pattern often complicates the patient's required dental procedures, induces stress in the dentist, and interferes with the dentist's ability to provide comprehensive care. 5 More importantly, the patient's oral health is significantly compromised due to avoidance.…”
mentioning
confidence: 99%
“…Reports have indicated that, in comparison to control groups, phobic patients present with more missing teeth, more tooth decay, fewer filled surfaces, more periradicular lesions, and more bone loss. 1,5 In addition, because dental providers lack sufficient knowledge in addressing anxiety-related psychological issues, dentist-patient rapport and the quality of care often suffer as a result. 6 Considering the ramifications of this problem, dental care providers need to acquire the ability to recognize and adequately manage patient anxiety.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that the predictive value of the chosen scales was 80% and that the risk of therapy failure increased about 11 times with an increase of one scale of the PACS (OR = 11.20; 95% CI = 1.70–73.10), about three times with an increase of one level of the mean DAS score (OR = 2.96; 95% CI = 1.15–7.63) and 0.17 times with an increase of one level of the SCL‐90R (OR = 0.17; 95% CI = 0.03–0.92). Ultimately, the study recommended that the scores be used as part of an initial admittance process for patients who suffer from dental anxiety to enhance the ability to recognise patients who are prone to fail behaviour therapy (25).…”
Section: Resultsmentioning
confidence: 99%